Nano hydroxyl cobalt oxide as well as preparation method and application thereof
By employing a technical approach involving synergistic confined growth with dual amines, mild oxidation and confined regeneration, surface silane grafting, and a two-stage polymer brush layer construction, the problems of large thickness and high interfacial impedance in CoOOH materials have been solved, resulting in nano-cobalt hydroxyl oxide materials with high rate performance and long cycle stability, suitable for lithium-ion batteries.
Patent Information
- Application Number
- CN202511463156.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-14
- Publication Date
- 2025-11-11
- Estimated Expiration
- 2045-10-14
AI Technical Summary
Existing CoOOH materials in lithium-ion batteries suffer from problems such as large thickness and high interfacial impedance, resulting in poor rate performance and short cycle life.
An integrated technical route is adopted, which involves synergistic confined growth of dual amines, mild oxidation and confined regeneration, surface silane grafting, and two-stage polymer brush layer construction. Through synergistic confined growth of n-butylamine and n-dodecylamine, mild oxidation treatment, surface silane grafting, and two-stage polymer brush layer construction, the thickness control and interface engineering optimization of nano-cobalt hydroxyoxide are achieved.
The ultra-thin thickness and low impedance interface structure of nano-cobalt hydroxyl oxide material were achieved, which improved the high-rate performance and long-cycle stability of lithium-ion batteries. The reversible capacity at 10C high rate reached more than 400mAh/g, and the capacity retention rate after 1000 cycles at 1C reached more than 80%.
Smart Images

Figure CN120922926A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, and in particular to a nano-cobalt hydroxyoxide, its preparation method, and its application. Background Technology
[0002] With the rapid development of electric vehicles, energy storage systems, and portable electronic devices, the demand for high-performance lithium-ion batteries is becoming increasingly urgent. Cobalt hydroxyoxide (CoOOH), as an important transition metal compound, has attracted widespread attention in the field of lithium-ion battery anode materials due to its advantages such as high theoretical specific capacity, abundant resources, and environmental friendliness. However, traditional CoOOH materials face key technical bottlenecks in practical applications, such as limited electron / ion transport and poor rate performance.
[0003] In existing technologies, the preparation of CoOOH materials mainly employs direct chemical oxidation or in-situ electrochemical methods, resulting mostly in nanosheet / nanosheet cluster structures. Although there are reports of using sodium hypochlorite to mildly oxidize β-Co(OH)₂ to β-CoOOH under alkaline conditions, and relatively well maintaining the morphology and size of the precursor, this mild external oxidation system still has significant limitations. First, traditional preparation methods struggle to precisely control the nanosheet thickness, resulting in typically thicker CoOOH materials that elongate the lithium-ion diffusion path, limiting the material's rate performance. Second, conventional preparation processes lack effective morphology control methods, failing to simultaneously achieve synergistic optimization of ultrathin thickness and high specific surface area, thus affecting the active site density and electrochemical reaction kinetics.
[0004] More importantly, existing CoOOH materials generally suffer from high interfacial impedance. During lithium-ion battery operation, the interfacial resistance between the electrode material and the electrolyte directly affects charge transfer efficiency and battery performance. Traditional CoOOH materials lack effective interface engineering design, resulting in insufficient microenvironment control at the electrode-electrolyte interface, leading to high interfacial resistance and severely limiting the material's rate performance and cycle stability. Especially under high-rate charge-discharge conditions, interfacial polarization intensifies, and electrochemical performance deteriorates sharply.
[0005] In interface engineering, existing technologies mainly employ simple surface coating or doping modifications, lacking precise interface structure design. These traditional modification methods often lead to a decrease in active material loading or weak bonding between the modified layer and the substrate, making it prone to detachment during cycling and affecting the long-term stability of the battery. In particular, there is a lack of effective means to precisely control the electrolyte microenvironment through surface functionalized molecules, failing to fundamentally solve the problem of high interfacial impedance.
[0006] In summary, existing technologies have significant gaps in areas such as precise thickness control and interface impedance optimization of CoOOH materials, and there is an urgent need to develop new preparation methods and technical routes to meet the stringent requirements of high-performance lithium-ion batteries for electrode materials. Summary of the Invention
[0007] In view of this, the purpose of this invention is to propose a nano-cobalt hydroxy oxide, its preparation method and application, in order to solve the problems of poor rate performance and short cycle life of lithium batteries caused by the large thickness and high interfacial impedance of existing CoOOH materials.
[0008] To achieve the above objectives, the present invention provides a method for preparing nano-cobalt hydroxyoxide, comprising the following steps: S1: Cobalt nitrate hexahydrate, urea, n-butylamine, n-dodecylamine and deionized water are stirred at room temperature for 25-35 min, then heated to 60-70℃ and stirred for 60-120 min, and cooled to room temperature to obtain a uniform suspension; S2: Add the uniform suspension obtained in step S1 to an aqueous sodium hydroxide solution, stir for 12-20 min, then keep stirring at 40-50℃ for 40-60 min, centrifuge, wash with water, and then disperse in an aqueous sodium hydroxide solution to obtain nano-Co(OH)2 precursor slurry. S3: Under ice bath conditions, alkaline sodium hypochlorite oxidizing solution is added dropwise to the nano Co(OH)2 precursor slurry obtained in step S2, heated to 12-18℃ and stirred for 20-30 min, centrifuged, washed, and nano CoOOH precursor A is obtained. S4: Add the nano-CoOOH precursor A obtained in step S3 to deionized water, then add n-butylamine, n-dodecylamine and urea, stir at 45-55℃ for 30-45 min, cool to room temperature, centrifuge, wash with water, then disperse in sodium hydroxide aqueous solution, add alkaline sodium hypochlorite oxidizing solution, stir for 25-35 min, centrifuge, wash, to obtain nano-CoOOH precursor B; S5: Add the nano-CoOOH precursor B obtained in step S4 to anhydrous ethanol, then add 3-chloropropyltrimethoxysilane and deionized water, react at 68-75℃ for 40-70 min under nitrogen protection, centrifuge, vacuum dry, then disperse in N,N-dimethylformamide, add p-toluenesulfonate sodium, react at 80-90℃ for 6-10 h under nitrogen protection, centrifuge, wash with water, vacuum dry to obtain nano-CoOOH precursor containing initiation sites; S6: Add the nano-CoOOH precursor containing the initiation site obtained in step S5 and 2-methyl-2-oxazoline to anhydrous acetonitrile, and react at 78-82℃ for 8-12 h under a nitrogen atmosphere. Then add 2-nonyl-2-oxazoline and continue the reaction at 78-82℃ for 8-12 h. Centrifuge, wash, and vacuum dry to obtain nano-cobalt hydroxyoxide.
[0009] Preferably, based on 16-20g of cobalt nitrate hexahydrate, the amount of urea added in step S1 is 20-30g, the amount of n-butylamine added is 6-10g, the amount of n-dodecylamine added is 3-6g, and the amount of deionized water added is 350-450mL.
[0010] Preferably, the concentration of the sodium hydroxide aqueous solution is 0.3 g / mL.
[0011] Preferably, based on 16-20g of cobalt nitrate hexahydrate, the first addition of sodium hydroxide aqueous solution in step S2 is 40-60mL, and the second addition of sodium hydroxide aqueous solution is 40-60mL.
[0012] Preferably, the alkaline sodium hypochlorite oxidation solution is prepared from sodium hypochlorite, sodium hydroxide and deionized water, and the ratio of sodium hypochlorite, sodium hydroxide and deionized water is 24-35g:12-18g:250mL.
[0013] Preferably, based on 16-20g of cobalt nitrate hexahydrate, the amount of alkaline sodium hypochlorite oxidation solution added in step S3 is 160-230mL.
[0014] Preferably, based on 16-20g of cobalt nitrate hexahydrate, the amount of deionized water added in step S4 is 280-350mL, the amount of n-butylamine added is 3-5g, the amount of n-dodecylamine added is 1.5-3g, the amount of urea added is 12-18g, the amount of sodium hydroxide aqueous solution added is 40-60mL, and the amount of alkaline sodium hypochlorite oxidation solution added is 20-30mL.
[0015] Preferably, based on 16-20g of cobalt nitrate hexahydrate, the amount of anhydrous ethanol added in step S5 is 130-180mL, the amount of 3-chloropropyltrimethoxysilane added is 2-4g, the amount of deionized water added is 0.8-1.5mL, the amount of N,N-dimethylformamide added is 140-180mL, and the amount of p-toluenesulfonate sodium added is 4-6g.
[0016] Preferably, based on 16-20g of cobalt nitrate hexahydrate, the amount of 2-methyl-2-oxazoline added in step S6 is 6-10g, the amount of 2-nonyl-2-oxazoline added is 6-10g, and the amount of anhydrous acetonitrile added is 100-140mL.
[0017] Furthermore, the present invention also provides a nano-cobalt hydroxyoxide obtained by the above-described method for preparing nano-cobalt hydroxyoxide.
[0018] This invention achieves significant improvements in thickness control, interface engineering, and electrochemical performance of nano-cobalt hydroxyl oxide materials through an integrated technical route of dual-amine synergistic confined growth, mild oxidation and confined regeneration repeated treatment, surface silane grafting, and two-stage polymer brush layer construction.
[0019] First, the technical advantage of the dual-amine synergistic confinement mechanism lies in its ability to precisely control the thickness of the nanosheets. n-Butylamine, through the interaction of amino groups and Co... 2+ The coordination effect of the compound confines the layered epitaxial growth, while dodecylamine utilizes its long-chain hydrophobic end to cap the edge of the lamellar layer. The two work synergistically to regulate the "hydrolysis-condensation-layered epitaxy" process, reducing the thickness of the prepared nano-cobalt hydroxyl oxide to an ultrathin range of 3-5 nm. This thickness control technology directly shortens the diffusion path of lithium ions, increases the specific surface area and active site density, and fundamentally improves the rate performance and first-cycle reversibility of the material.
[0020] Secondly, the innovation of the alkaline sodium hypochlorite mild oxidation and confined regrowth-re-oxidation repetitive treatment technology lies in the introduction of controllable structural defects while maintaining the integrity of the layered lattice. This mild stepwise oxidation avoids the structural damage that may be caused by strong one-time oxidation. Through repetitive treatment, appropriate amounts of hydroxyl vacancies and controllable mismatches are introduced into the interlayer, forming active channels that are conducive to ion / electron transport. This technology significantly reduces charge transfer impedance and improves capacity utilization under high-rate conditions.
[0021] Third, the surface silane grafting technology constructs controllable initiation sites using 3-chloropropyltrimethoxysilane, which, after activation by p-toluenesulfonate, provides uniformly distributed anchoring points for subsequent polymerization reactions. This surface functionalization strategy ensures strong adhesion between the polymer brush layer and the matrix, avoiding the problem of easy detachment of the modified layer in traditional surface modification and improving the stability of the interface structure.
[0022] Fourth, the two-stage poly(2-oxazoline) brush layer construction technology enables precise control of the electrode-electrolyte microenvironment. First, 2-methyl-2-oxazoline is polymerized to form a hydrophilic inner layer, providing a good lithium-ion transport channel; then, 2-nonyl-2-oxazoline is polymerized to form a hydrophobic outer layer, acting as a selective barrier. This hydrophilic-hydrophobic dual-block structure optimizes interfacial stability, significantly reduces interfacial resistance, and suppresses side reactions while ensuring ion transport efficiency.
[0023] Most importantly, this invention, through the integrated coupling design of process timing, constructs a low-impedance, anti-attenuation interface structure while maintaining the lattice layered characteristics and ultrathin nanosheets. This allows the material to maintain a reversible capacity of over 400 mAh / g at a high rate of 10C, and a capacity retention rate of over 80% after 1000 cycles at 1C. This achieves an effective balance between high-rate performance and long-cycle stability, providing important technical support for the industrial application of high-performance lithium-ion battery electrode materials. Attached Figure Description
[0024] To more clearly illustrate the technical solutions in this invention or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below.
[0025] Figure 1 The X-ray diffraction pattern of nano-cobalt hydroxyl oxide in Example 2 of this invention; Figure 2 The infrared spectra of nano-CoOOH precursor B and nano-cobalt hydroxyoxide in Example 2 of this invention are shown. Detailed Implementation
[0026] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.
[0027] Example 1: (1) Add 350 mL of deionized water, 16 g of cobalt nitrate hexahydrate and 20 g of urea to a 1000 mL beaker in sequence. After stirring and dissolving, add 6 g of n-butylamine and 3 g of n-dodecylamine. Stir at room temperature for 25 min, then heat to 60 °C and keep stirring for 60 min. Cool to room temperature to obtain a uniform suspension. (2) Add the uniform suspension obtained in step (1) to 40 mL of sodium hydroxide aqueous solution (concentration of 0.3 g / mL), stir for 12 min, keep stirring at 40 °C for 40 min, centrifuge, wash with water 3 times, and then disperse in 40 mL of sodium hydroxide aqueous solution (concentration of 0.3 g / mL) to obtain nano Co(OH)2 precursor slurry; (3) Dissolve 24g sodium hypochlorite and 12g sodium hydroxide in 250mL of deionized water to obtain an alkaline sodium hypochlorite oxidation solution; (4) Under ice bath conditions, 160 mL of alkaline sodium hypochlorite oxidizing solution was added dropwise to the nano Co(OH)2 precursor slurry obtained in step (2), stirred at 12 °C for 20 min, centrifuged, and washed twice with anhydrous ethanol to obtain nano CoOOH precursor A. (5) Add the nano-CoOOH precursor A obtained in step (4) to 280 mL of deionized water, 3 g of n-butylamine, 1.5 g of n-dodecylamine and 12 g of urea, stir at 45 °C for 30 min to trigger the confined regrowth process, cool to room temperature, centrifuge, wash with water 3 times, disperse in 40 mL of sodium hydroxide aqueous solution (concentration of 0.3 g / mL), add 20 mL of alkaline sodium hypochlorite oxidizing solution, stir for 25 min, centrifuge, wash with anhydrous ethanol twice to obtain nano-CoOOH precursor B; (6) Add the nano-CoOOH precursor B obtained in step (5) to 130 mL of anhydrous ethanol, then add 2 g of 3-chloropropyltrimethoxysilane and 0.8 mL of deionized water, react at 68 °C for 40 min under nitrogen protection, centrifuge, dry under vacuum at 60 °C for 6 h, disperse in 140 mL of N,N-dimethylformamide, add 4 g of p-toluenesulfonate sodium, react at 80 °C for 6 h under nitrogen protection, centrifuge, wash 3 times with deionized water, dry under vacuum at 60 °C for 12 h to obtain nano-CoOOH precursor containing initiation sites; (7) Add the nano-CoOOH precursor containing the initiation site obtained in step (6) and 6g of 2-methyl-2-oxazoline to 100mL of anhydrous acetonitrile. Under a nitrogen atmosphere, react at 78℃ for 8h. Then add 6g of 2-nonyl-2-oxazoline and continue to react at 78℃ for 8h. After centrifugation, wash three times with anhydrous ethanol and dry under vacuum at 60℃ for 12h to obtain nano-cobalt hydroxyoxide.
[0028] Example 2: (1) Add 400 mL of deionized water, 18 g of cobalt nitrate hexahydrate and 25 g of urea to a 1000 mL beaker in sequence. After stirring and dissolving, add 8 g of n-butylamine and 4 g of n-dodecylamine. Stir at room temperature for 30 min, then heat to 65 °C and keep stirring for 90 min. Cool to room temperature to obtain a uniform suspension. (2) Add the uniform suspension obtained in step (1) to 50 mL of sodium hydroxide aqueous solution (concentration of 0.3 g / mL), stir for 15 min, keep stirring at 45 °C for 45 min, centrifuge, wash with water 3 times, and then disperse in 50 mL of sodium hydroxide aqueous solution (concentration of 0.3 g / mL) to obtain nano Co(OH)2 precursor slurry; (3) Dissolve 30g of sodium hypochlorite and 15g of sodium hydroxide in 250mL of deionized water to obtain an alkaline sodium hypochlorite oxidizing solution; (4) Under ice bath conditions, 200 mL of alkaline sodium hypochlorite oxidizing solution was added dropwise to the nano Co(OH)2 precursor slurry obtained in step (2), stirred at 15 °C for 25 min, centrifuged, and washed twice with anhydrous ethanol to obtain nano CoOOH precursor A. (5) Add the nano-CoOOH precursor A obtained in step (4) to 300 mL of deionized water, 4 g of n-butylamine, 2 g of n-dodecylamine and 15 g of urea, stir at 50 °C for 35 min to trigger the confined regrowth process, cool to room temperature, centrifuge, wash with water 3 times, disperse in 50 mL of sodium hydroxide aqueous solution (concentration of 0.3 g / mL), add 30 mL of alkaline sodium hypochlorite oxidizing solution, stir for 30 min, centrifuge, wash with anhydrous ethanol twice to obtain nano-CoOOH precursor B; (6) Add the nano-CoOOH precursor B obtained in step (5) to 150 mL of anhydrous ethanol, then add 3 g of 3-chloropropyltrimethoxysilane and 1 mL of deionized water, react at 70 °C for 50 min under nitrogen protection, centrifuge, dry under vacuum at 60 °C for 6 h, disperse in 150 mL of N,N-dimethylformamide, add 5 g of p-toluenesulfonate sodium, react at 85 °C for 8 h under nitrogen protection, centrifuge, wash 3 times with deionized water, dry under vacuum at 60 °C for 12 h to obtain nano-CoOOH precursor containing initiation sites; (7) Add the nano-CoOOH precursor containing the initiation site obtained in step (6) and 8g of 2-methyl-2-oxazoline to 120mL of anhydrous acetonitrile, and react at 80℃ for 10h under nitrogen atmosphere. Then add 8g of 2-nonyl-2-oxazoline and continue to react at 80℃ for 10h. After centrifugation, wash three times with anhydrous ethanol and dry under vacuum at 60℃ for 12h to obtain nano-cobalt hydroxy oxide.
[0029] Example 3: (1) Add 450 mL of deionized water, 20 g of cobalt nitrate hexahydrate and 30 g of urea to a 1000 mL beaker in sequence. After stirring and dissolving, add 10 g of n-butylamine and 6 g of n-dodecylamine. Stir at room temperature for 35 min, then heat to 70 °C and keep stirring for 120 min. Cool to room temperature to obtain a uniform suspension. (2) Add the uniform suspension obtained in step (1) to 60 mL of sodium hydroxide aqueous solution (concentration of 0.3 g / mL), stir for 20 min, keep stirring at 50 °C for 60 min, centrifuge, wash with water 3 times, and then disperse in 60 mL of sodium hydroxide aqueous solution (concentration of 0.3 g / mL) to obtain nano Co(OH)2 precursor slurry; (3) Dissolve 36g of sodium hypochlorite and 18g of sodium hydroxide in 250mL of deionized water to obtain an alkaline sodium hypochlorite oxidizing solution; (4) Under ice bath conditions, 230 mL of alkaline sodium hypochlorite oxidizing solution was added dropwise to the nano Co(OH)2 precursor slurry obtained in step (2), stirred at 18°C for 30 min, centrifuged, and washed twice with anhydrous ethanol to obtain nano CoOOH precursor A. (5) Add the nano-CoOOH precursor A obtained in step (4) to 350 mL of deionized water, 5 g of n-butylamine, 3 g of n-dodecylamine and 18 g of urea, stir at 55 °C for 45 min to trigger the confined regrowth process, cool to room temperature, centrifuge, wash with water 3 times, disperse in 60 mL of sodium hydroxide aqueous solution (concentration of 0.3 g / mL), add 20 mL of alkaline sodium hypochlorite oxidizing solution, stir for 35 min, centrifuge, wash with anhydrous ethanol twice to obtain nano-CoOOH precursor B; (6) Add the nano-CoOOH precursor B obtained in step (5) to 180 mL of anhydrous ethanol, then add 4 g of 3-chloropropyltrimethoxysilane and 1.5 mL of deionized water, react at 75 °C for 70 min under nitrogen protection, centrifuge, dry under vacuum at 60 °C for 6 h, disperse in 180 mL of N,N-dimethylformamide, add 6 g of p-toluenesulfonate sodium, react at 90 °C for 10 h under nitrogen protection, centrifuge, wash 3 times with deionized water, dry under vacuum at 60 °C for 12 h to obtain nano-CoOOH precursor containing initiation sites; (7) Add the nano-CoOOH precursor containing the initiation site obtained in step (6) and 10g of 2-methyl-2-oxazoline to 140mL of anhydrous acetonitrile. Under a nitrogen atmosphere, react at 82℃ for 12h. Then add 10g of 2-nonyl-2-oxazoline and continue to react at 82℃ for 12h. After centrifugation, wash three times with anhydrous ethanol and dry under vacuum at 60℃ for 12h to obtain nano-cobalt hydroxy oxide.
[0030] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that n-dodecylamine is not added in step (the amount is changed to 0g), only n-butylamine 12g is added, and the other conditions are the same as in Example 2.
[0031] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that n-butylamine is not added in step (the amount is changed to 0g), only 12g of n-dodecylamine is added, and the other conditions are the same as in Example 2.
[0032] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that the "confined regrowth-re-oxidation" process is cancelled, that is, step (5) is omitted, and the nano-CoOOH precursor A obtained in step (4) is directly used to enter step (6), while the other conditions are the same as in Example 2.
[0033] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that the low temperature control is cancelled, and in step (4), alkaline oxidizing liquid is added dropwise at 25°C and stirred for 25 minutes. The other conditions are the same as in Example 2.
[0034] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is that silane grafting is not performed, step (6) is omitted, and the polymerization reaction conditions of the nano-CoOOH precursor B obtained in step (5) are directly used to attempt polymerization. The remaining conditions are the same as those in Example 2.
[0035] Comparative Example 6: The difference between Comparative Example 6 and Example 2 is that surface polymerization only involves the first monomer stage, and in step (7), only 16g of 2-methyl-2-oxazoline is added and reacted for 10h, without adding 2-nonyl-2-oxazoline. The other conditions are the same as in Example 2.
[0036] Comparative Example 7: The difference between Comparative Example 7 and Example 2 is that surface polymerization only involves the second monomer stage, and in step (7), only 16g of 2-nonyl-2-oxazoline is added and reacted for 10h, without adding 2-methyl-2-oxazoline. The other conditions are the same as in Example 2.
[0037] Performance testing: The electrode sheets used in the following tests all used active materials (Examples 1-3 or corresponding comparative samples): SuperP conductive agent:PVDF binder = 8:1:1 (mass ratio), NMP slurry, uniformly coated on copper foil, dried, vacuum dried at 120℃ for 12h, and rolled to an areal density of 1.5mg / cm³. 2 Coin cell CR2032 half-cells (lithium foil counter electrode, Celgard separator, 1M LiPF6 / EC:DEC=1:1, containing 5wt% FEC) were tested after standing at 25℃ for 12 hours. Each sample had ≥3 parallel groups, and the average value was given.
[0038] X-ray diffraction test: The test results using a powder X-ray diffractometer are as follows... Figure 1 As shown.
[0039] Infrared spectroscopy test: The test was conducted using an infrared spectrometer, and the results are as follows: Figure 2 As shown.
[0040] Thickness of nano-cobalt hydroxyl oxide: The thickness of nano-cobalt hydroxyl oxide was measured using atomic force microscopy. The test was conducted in tapping mode, with a silicon probe elastic modulus of 42 N / m, a resonant frequency of approximately 320 kHz, a scan rate of 0.5 Hz, and a scan range of 5 μm × 5 μm. The average thickness was measured through statistical analysis of at least 200 individual nanosheets, and the results are shown in Table 1.
[0041] Specific surface area test: The specific surface area of nano-cobalt hydroxyl oxide was tested using the nitrogen adsorption BET method at 77 K. The relative pressure range was P / P0 = 0.01-0.99. The BET specific surface area was calculated using the linear range of P / P0 = 0.05-0.30. The results are shown in Table 1.
[0042] Electrode surface resistance: The sheet resistance was measured on the electrode coating side using the four-probe method with a probe spacing of 1.0 mm and a steady-state value obtained by linear scanning with a current range of 1-10 mA. The results are shown in Table 1.
[0043] Rate performance: Rate performance tests were conducted in the sequence of 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, and 10C, with each rate cycled 5 times. Finally, the test was performed at 0.1C to verify the capacity recovery capability. The capacity was calculated by integrating the discharge platform. The reversible specific capacity and capacity recovery rate at the high rate of 10C were recorded. The results are shown in Table 1.
[0044] Cyclic stability test: 1000 charge-discharge cycles were performed at 1C rate, and the capacity retention rate was calculated based on the initial effective capacity. The results are shown in Table 1.
[0045]
[0046] Data Analysis: As can be seen from the data in Examples 1-3 of Table 1, the nano-cobalt hydroxyl oxide prepared by this invention exhibits significant performance tunability under the comprehensive control of the diamine synergistic confinement system and surface modification engineering, demonstrating the effectiveness of process parameter optimization. With the systematic adjustment of the diamine ratio, oxidation conditions, and polymerization parameters, the nanosheet thickness, specific surface area, sheet resistivity, and electrochemical performance show regular changing trends. Among them, Example 2 obtained the best comprehensive performance, indicating the existence of an optimal process parameter window. This performance tunability may stem from the precise control of nanosheet thickness by the diamine synergistic confinement mechanism during the hydrolysis-condensation-layered epitaxy process, and the introduction of controllable ion / electron active channels while maintaining the layered lattice through the mild sodium hypochlorite oxidation and confinement regrowth-re-oxidation repetitive treatment. Surface silane grafting and the construction of a two-segment poly(2-oxazoline) brush layer further optimized the electrode-electrolyte interface, regulating the microenvironment and reducing interfacial impedance through a hydrophilic-hydrophobic dual-block structure.
[0047] As can be seen from the data in Table 1 for Example 2 and Comparative Example 1, the dual-amine synergistic confinement strategy exhibits significant advantages over the single n-butylamine system in terms of nanosheet morphology control and electrochemical performance, highlighting the importance of synergistic regulation of long and short chain amine molecules. Comparative analysis shows that the dual-amine system demonstrates significant technical effects in thickness control, specific surface area improvement, interfacial resistance reduction, and rate performance improvement. This may be related to the synergistic mechanism of n-butylamine amino-coordination confinement of layered epitaxy and n-dodecylamine long-chain hydrophobic end-capping of the sheet edges. When n-butylamine is used alone, although the amino coordination can limit layered growth to some extent, the lack of end-capping effect from long-chain amines leads to less precise control of sheet thickness, a relatively low specific surface area, and increased inter-sheet contact resistance. The difference in electrochemical performance indicates that the ultrathin nanosheet structure constructed by the dual-amine synergistic system provides lithium ions with a shorter diffusion path and more active sites, while also improving charge transfer kinetics. The improved rate performance and cycling stability may stem from the more uniform and stable nanosheet structure formed under the regulation of diamines, and the resulting improvement in electrode density and structural stability, demonstrating the key role of the diamine synergistic confinement mechanism in the preparation of ultrathin layered materials.
[0048] As can be seen from the data in Example 2 and Comparative Example 2 in Table 1, when only long-chain n-dodecylamine is used, the nanosheet thickness increases significantly, the specific surface area decreases sharply, the sheet resistivity increases sharply, and the electrochemical performance deteriorates severely. This indicates that relying solely on the end-capping effect of the hydrophobic long chain cannot achieve effective thickness confinement. This performance degradation may be directly related to the lack of coordination of the n-butylamine amino group. During the hydrolysis-condensation-layered epitaxy process, the lack of coordination confinement by the short-chain amine makes it difficult to control the hydrolysis and condensation process of cobalt ions, resulting in thicker nanosheets and a relatively rough surface morphology. Although long-chain n-dodecylamine has hydrophobic end-capping ability, its coordination ability is relatively weak and cannot effectively regulate layered growth on its own. The significant decrease in electrochemical performance reflects the adverse effect of the thick nanosheet structure on lithium-ion diffusion kinetics. The increased thickness prolongs the ion diffusion path, the reduced specific surface area decreases the density of active sites, and the high sheet resistivity indicates that inter-sheet contact and electron transport are severely hindered.
[0049] As can be seen from the data in Example 2 and Comparative Example 3 in Table 1, when the confinement regrowth process is omitted and surface modification is performed directly, although the nanosheet thickness remains relatively thin, the specific surface area decreases, the surface resistivity increases significantly, and the electrochemical performance declines markedly. This indicates that a single oxidation treatment cannot fully optimize the microstructure and interfacial properties of the nanosheets. This may be because the initial mild oxidation converts Co(OH)2 into a preliminary CoOOH structure, the confinement regrowth process achieves the repair of lattice defects and further optimization of surface morphology through the reintroduction of the diamine system, and the re-oxidation introduces more ionic / electron active channels while maintaining the optimized morphology. This iterative treatment avoids the structural damage that may be caused by a single strong oxidation, and through mild stepwise treatment, it introduces an appropriate amount of hydroxyl vacancies and interlayer mismatches while maintaining the integrity of the layered lattice, thereby improving charge storage and transport properties.
[0050] As can be seen from the data in Example 2 and Comparative Example 4 in Table 1, when the oxidation reaction was carried out at room temperature, the thickness of the nanosheets increased slightly, the specific surface area decreased, and the sheet resistivity remained relatively low, but the electrochemical performance deteriorated significantly, especially the rate performance and cycle stability. This indicates that temperature control is crucial for maintaining the structural integrity and electrochemical stability of the nanosheets. This may be because, under ice bath conditions, the oxidation rate of sodium hypochlorite was effectively controlled, avoiding local over-oxidation and structural defects that could be caused by an excessively rapid oxidation reaction, resulting in a more uniform and mild conversion process from Co(OH)₂ to CoOOH.
[0051] As can be seen from the data in Example 2 and Comparative Example 5 in Table 1, when surface polymerization is carried out directly without silane grafting, the thickness and specific surface area of the nanosheets remain basically the same, but the sheet resistivity increases significantly, and the rate performance and cycle stability decrease significantly. This indicates that silanization treatment has a decisive influence on the interface engineering and surface modification effects. Without silane grafting, the direct polymerization reaction lacks effective initiation sites and interfacial bonding forces, resulting in the inability of polymer chains to form a uniform and dense brush layer structure on the nanosheet surface.
[0052] As can be seen from the data in Table 1 for Examples 2, 6, and 7, the two-stage polymerization strategy demonstrates superior interface control compared to single polymerization, highlighting the importance of the hydrophilic-hydrophobic diblock structure. The technical advantage of the two-stage polymerization likely stems from the precise control of the electrolyte microenvironment by the hydrophilic-hydrophobic diblock structure: the first stage, the hydrophilic inner layer formed by 2-methyl-2-oxazoline, provides excellent lithium-ion transport channels and electrolyte wettability, ensuring basic electrochemical reactivity; the second stage, the hydrophobic outer layer formed by 2-nonyl-2-oxazoline, acts as a selective barrier, regulating the distribution and diffusion behavior of the electrolyte on the electrode surface and potentially inhibiting certain side reactions, thus improving interfacial stability. This gradient interfacial structure optimizes the long-term stability and anti-attenuation capability of the electrode while ensuring ion transport efficiency.
[0053] from Figure 1 It can be seen that the sample exhibits typical layered CoOOH diffraction characteristics, with a strong and significantly broadened (003) peak near 20.2°, and diffraction peaks of (101), (012), (015), (110), and (113) appearing successively at 37.0°, 38.9°, 50.7°, 65.4°, and 69.3°, indicating that the product is a rhombohedral polymorphic CoOOH phase. Due to the material being an ultrathin nanosheet, the (003) peak is significantly broadened. At the same time, the crescent-shaped background in the 15–30° range and the slight granular noise at the peak top are consistent with the amorphous scattering and noise characteristics caused by the surface poly(2-oxazoline) brush layer and adsorbed water.
[0054] from Figure 2 It can be seen that, compared to precursor B, the modified nano-cobalt hydroxyl oxide at 1648 cm⁻¹... -1 A distinct new absorption peak appears at 1105 cm⁻¹ (attributed to the amide-like C=O of poly(2-oxazoline)). -1 With approximately 1030cm -1 A COC and Si-O-Si overlapping reinforcement band appears at 2920 / 2850 cm⁻¹. -1 The CH stretching peaks were also significantly enhanced, indicating the successful introduction of silane anchoring and the polymerized brush layer; meanwhile, both peaks at 620 / 520 cm⁻¹ were also significantly enhanced. -1 The Co-O framework vibrations were all preserved, indicating that the surface modification did not alter the layered framework of CoOOH. The modified sample exhibited a wide OH band (~3405 cm⁻¹). -1 The relative reduction in H2O bending zone (~1630cm) -1 The portion of the surface is covered by C=O absorption, reflecting the regulatory effect of the brush layer on the interfacial hydroxyl groups and adsorbed water.
[0055] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of the invention is limited to these examples; within the framework of the invention, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of the different aspects of the invention as described above, which are not provided in detail for the sake of brevity.
Claims
1. A method for preparing nano-cobalt hydroxyoxide, characterized in that, Includes the following steps: S1: Cobalt nitrate hexahydrate, urea, n-butylamine, n-dodecylamine and deionized water are stirred at room temperature for 25-35 min, then heated to 60-70℃ and stirred for 60-120 min, and cooled to room temperature to obtain a uniform suspension; S2: Add the uniform suspension obtained in step S1 to an aqueous sodium hydroxide solution, stir for 12-20 min, then keep stirring at 40-50℃ for 40-60 min, centrifuge, wash with water, and then disperse in an aqueous sodium hydroxide solution to obtain nano-Co(OH)2 precursor slurry. S3: Under ice bath conditions, alkaline sodium hypochlorite oxidizing solution is added dropwise to the nano Co(OH)2 precursor slurry obtained in step S2, heated to 12-18℃ and stirred for 20-30 min, centrifuged, washed, and nano CoOOH precursor A is obtained. S4: Add the nano-CoOOH precursor A obtained in step S3 to deionized water, then add n-butylamine, n-dodecylamine and urea, stir at 45-55℃ for 30-45 min, cool to room temperature, centrifuge, wash with water, then disperse in sodium hydroxide aqueous solution, add alkaline sodium hypochlorite oxidizing solution, stir for 25-35 min, centrifuge, wash, to obtain nano-CoOOH precursor B; S5: Add the nano-CoOOH precursor B obtained in step S4 to anhydrous ethanol, then add 3-chloropropyltrimethoxysilane and deionized water, react at 68-75℃ for 40-70 min under nitrogen protection, centrifuge, vacuum dry, then disperse in N,N-dimethylformamide, add p-toluenesulfonate sodium, react at 80-90℃ for 6-10 h under nitrogen protection, centrifuge, wash with water, vacuum dry to obtain nano-CoOOH precursor containing initiation sites; S6: Add the nano-CoOOH precursor containing the initiation site obtained in step S5 and 2-methyl-2-oxazoline to anhydrous acetonitrile, and react at 78-82℃ for 8-12 h under nitrogen atmosphere. Then add 2-nonyl-2-oxazoline and continue to react at 78-82℃ for 8-12 h. Centrifuge, wash, and vacuum dry to obtain nano-cobalt hydroxyoxide. Based on 16-20g of cobalt nitrate hexahydrate; In step S1, the amount of urea added is 20-30g, the amount of n-butylamine added is 6-10g, the amount of n-dodecylamine added is 3-6g, and the amount of deionized water added is 350-450mL. In step S4, the amount of deionized water added is 280-350 mL, the amount of n-butylamine added is 3-5 g, the amount of n-dodecylamine added is 1.5-3 g, the amount of urea added is 12-18 g, the amount of sodium hydroxide aqueous solution added is 40-60 mL, and the amount of alkaline sodium hypochlorite oxidizing solution added is 20-30 mL. In step S6, the amount of 2-methyl-2-oxazoline added is 6-10g, the amount of 2-nonyl-2-oxazoline added is 6-10g, and the amount of anhydrous acetonitrile added is 100-140mL.
2. The method for preparing nano-cobalt hydroxyl oxide according to claim 1, characterized in that, The concentration of the sodium hydroxide aqueous solution is 0.3 g / mL.
3. The method for preparing nano-cobalt hydroxyl oxide according to claim 1, characterized in that, Based on 16-20g of cobalt nitrate hexahydrate, the first addition of sodium hydroxide aqueous solution in step S2 is 40-60mL, and the second addition of sodium hydroxide aqueous solution is 40-60mL.
4. The method for preparing nano-cobalt hydroxyl oxide according to claim 1, characterized in that, The alkaline sodium hypochlorite oxidation solution is prepared by sodium hypochlorite, sodium hydroxide and deionized water, and the ratio of sodium hypochlorite, sodium hydroxide and deionized water is 24-35g:12-18g:250mL.
5. The method for preparing nano-cobalt hydroxyl oxide according to claim 1, characterized in that, Based on 16-20g of cobalt nitrate hexahydrate, the amount of alkaline sodium hypochlorite oxidation solution added in step S3 is 160-230mL.
6. The method for preparing nano-cobalt hydroxyl oxide according to claim 1, characterized in that, Based on 16-20g of cobalt nitrate hexahydrate, the amount of anhydrous ethanol added in step S5 is 130-180mL, the amount of 3-chloropropyltrimethoxysilane added is 2-4g, the amount of deionized water added is 0.8-1.5mL, the amount of N,N-dimethylformamide added is 140-180mL, and the amount of p-toluenesulfonate sodium added is 4-6g.
7. A nano-cobalt hydroxyl oxide, characterized in that, It is obtained by the preparation method of nano-cobalt hydroxyoxide according to any one of claims 1-6.
Citation Information
Patent Citations
Magnetic porous cobalt hollow ball electromagnetic wave absorption material, preparation method and application thereof
CN103586460A
Azobisformamide ratio fluorescence detection method based on CoOOH nanosheet loaded Au nano-cluster material
CN119804403A
Method for preparing positive active material for lithium secondary battery, positive active material prepared using same, and lithium secondary battery including same
KR1020100108850A